Health Services Research and Methodologies in Planning for Medical Care Facilities. Some International Comparisons - SCHICKE, R. K. (Methods of Information in Medicine, 1971)
This paper is devoted to the analysis of a variety of research issues and methods encountered in planning for stationary health facilities in the context of different national settings. This background information is presented to assist in selecting appropriate methods in dealing with planning problems and research programs.While Part I concentrates on conceptual issues of research in planning, the main theme of Part II is of an empirical nature focusing on the description of a specific statewide and regional planning task, utilizing inquiry media suitable for electronic data processing (EDP) and presented here mainly for purposes of illustration.
Keywords: Hospital Planning; Health Services Research; EDP in Hospital Planning; Planning Methods